Die politische Ökologie des Treibhauses in der russischen Literatur - Günther, Clemens (Wiener Slawistischer Almanach, 2023)
The article develops a problem-oriented approach to the motif history of thegreenhouse in Russian literature between the mid-nineteenth century and the OctoberRevolution. It shows how, during this period, the greenhouse became an ecological andpolitical figure of reflection, with the help of which social change and its accompanyingproblems such as exploitation, atmospheric changes, the destruction of biospheres, orthe possibility and necessity of revolutionary change were discussed. At the center of thefive case analyses are stories and novels by Ivan Turgenev, Vsevolod Garšin, AleksandrKuprin, Fedor Sologub, and Mikhail Bulgakov, each of which is situated in cultural andliterary history and analyzed with regard to its inherent political ecologies.